Strategic Thinking in a Hospital Setting - Hamdan, A. L. (Springer International Publishing : Imprint: Springer, 2017)
Translating the realities of healthcare reform and healthcare costs into competitive hospital practice is the goal of this accessible, jargon-free guide. Taking its cue from Michael Porter's highly-regarded business strategies, it offers a sound framework for hospitals looking to develop efficient, patient-centered service delivery, identifying keys to clinical, administrative, and marketing success. The book organizes business and clinical priorities where they intersect so that physicians throughout healthcare systems can understand their role in building and sustaining innovation, and leverage their strengths and system resources toward meeting patient needs. In addition, chapters review eight core strategic tools, describe possibilities for their implementation, and provide in-depth findings on Porter's methods as used in a diverse group of hospitals across Lebanon. Included in the coverage: · Porter's strategies in health care: cost leadership versus differentiation strategy · Sources of competitive advantage · How to prepare an organization for innovation · Strategic framework in a hospital setting · Application of Porter's strategies in Lebanese hospitals · Correlation between type of strategy and performance A well-designed blueprint for enhancing patient satisfaction and system cost-effectiveness, Strategic Thinking in a Hospital Setting is aimed at both frontline physicians in practice and those assuming administrative positions in healthcare facilities and in hospital settings in particular. .
Keywords: Medicine.; Health care management.; Health services administration.; Health administration.; Practice of medicine.; elektronické knihy; electronic books